Strategi Pengembangan Pendidikan - Ahsan, Muhammad Nur (Al-Riwayah : Jurnal Kependidikan, 2016)
Educational development should anticipate global tendency that will happen. Some trends can be identified, namely: (1) the process of investment and reinvestment, (2) the development of industry, communications and information, (3) a shift of education from back to basic to forward to future basics, which relies on improving the ability of TLC ( How to think, how to learn, and how to create), (4) the development and spreading the idea of democratization that gave rise to the demands of the implementation of school based management and site-specific solution, and (5) requires the way to solve the problem in analysis system, which not only rely on the analysis of cause and effect. The trends mentioned above requires a different quality of human resources with a quality that is today. So the question that is arises is whether our education produces graduates with adequate quality